The Effect of Intervention on Pregnancy with Diabetes Mellitus on Health-Related Quality of Life (HRQoL) - Devangga Darma Karingga; Achmad Wahdi; Dewi Retno Puspitosari; Kun Ika Nur Rahayu; Rahma Kusuma Dewi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2025)
Gestational diabetes mellitus (GDM) is a form of hyperglycemia that develops during pregnancy and is associated with maternal and neonatal complications. Women with GDM face increased risks of cesarean delivery, preeclampsia, and mental health issues, while their infants are more prone to macrosomia, neonatal jaundice, and long-term metabolic disorders. This systematic review evaluates the impact of interventions on the health-related quality of life (HRQoL) of pregnant women with diabetes mellitus. A systematic search in Scopus, SAGE, ScienceDirect, and ProQuest was conducted for studies published between 2021 and 2025, following PRISMA 2023 guidelines. From 611,094 initial records, 36 studies met the inclusion criteria, with five selected for in-depth analysis. The JBI critical appraisal tool was used to assess the validity and reliability of findings. Results indicate that digital health interventions, such as mobile fitness applications, improve adherence to pelvic floor exercises, enhancing physical health. Psychological interventions, including self-transcendence nursing models and cognitive-behavioral therapy, effectively reduce stress and enhance emotional well-being. Cardiovascular monitoring is essential, as GDM increases the risk of cardiac complications. Counseling, both face-to-face and app-based, supports self-care and lowers fasting blood glucose levels. In conclusion, a multidisciplinary approach integrating digital technology, psychosocial support, and cardiovascular monitoring is crucial for optimizing maternal and fetal health. Comprehensive care strategies, supported by policy frameworks, can enhance intervention effectiveness and improve the overall quality of life for women with GDM.